KONSISTENSI APLIKASI TAFSIR DALAM PEMERINTAHAN KARYA A. BUSYRO KARIM DALAM TAFSIR TRADISIONALIS: Membumikan Teks dalam Konteks Kehidupan Sosial dan Aplikasinya dalam Membangun Sumenep Periode 2010-2015 - Fadhilatul Aini; Ulya Fikriyati (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2024)
This article discusses the interpretation of the social theme by A. Busyro Karim, former regent of Sumenep, with kiai of pesantren and politician background. It will be extremely interesting, for the interpretations done were influenced by his experience as a social activist, exactly when he served as the regent of Sumenep. It is such a rare interpretation, for the simple reason that in a time when loads of people assumed that politic was full of conspiracy as a cunning stratagem, he brought al-Quran to have a dialog with social problems and made it as a foundation to shape the lives of people. At least, this article will answer two questions that is how was the idea of A. Busyro Karim in Traditionalist Interpretation: grounding the texts in the context of social life in the realm of religion, education, and health? In addition, how was his reasoning consistent with his social life reality in building Sumenep from 2010 to 2015? This article is a literature review with Adabi Ijtima’I Amin al-Khuli approach for analyzing the relationship as well as the reasoning consistency of A. Busyro Karim with his government policy towards the people. From this research, it is found that a strong social study of A. Busyro Karim’s interpretations were mostly influenced by his background as kiai of pesantren, organizational person, and social activist which demanded him to frequently interact with people. Accordingly, there are loads of relationships between his ideas in his interpretations with his wisdom during the time he served as the 2010-2015 regent of Sumenep. The moral values of the verses of al-Quran he understood were applied in the form of superior programs for people’s prosperity in Sumenep.